Definitive radiotherapy with stereotactic or IMRT boost with or without radiosensitization strategy for operable breast cancer patients who refuse surgery. (16th July 2022) - Shibamoto, Yuta; Takano, Seiya; Iida, Masato; Urano, Misugi; Ohta, Kengo; Oguri, Masanosuke; Murai, Taro
Abstract: For breast cancer (BC) patients who refused surgery, we developed a definitive treatment employing modern sophisticated radiation techniques. Thirty-eight operable BC patients were treated by conventionally fractionated whole-breast (WB) radiotherapy in combination with stereotactic (for primary tumor) or intensity-modulated (for primary tumor with/without regional lymph nodes [LN]) radiotherapy (IMRT) boost. Standard doses were 50 Gy/25 fractions, 21 Gy/3 fractions and 20 Gy/8 fractions, respectively, for the three radiation modalities. Disease stages were 0 (ductal carcinoma in situ [DCIS]) in seven patients, I in 12, II in 16 and III in three. In 26 patients, intratumoral hydrogen peroxide injection or hyperthermia with oral tegafur-gimeracil-oteracil potassium (S-1) was also used to sensitize the tumors to radiation. Hormonal and standard systemic therapy were administered in 25 and 13 patients, respectively. Complete and partial responses were obtained in 19 patients each; in patients with partial response, no further regrowth of the residual mass was observed, except for two patients who developed local recurrence. During a follow-up of 8–160 months (median, 50 months for living patients), two, one and two patients developed local relapse, sub-clavicular node metastasis and distant metastasis, respectively. The 5-year rates for overall, progression-free and local relapse-free survival were 97.2, 90.9 and 93.4%, respectively. Fourteen patients developed Grade 3 radiation dermatitis but all recovered after treatment. In 47%, the affected breast became better-rounded, and the nipple of the irradiated breast became higher by ≥1 cm than the contralateral nipple. Our method might be a treatment option for operable BC patients.